A STUDY OF SCHEDULING AND MANAGING DATA BASED CLOUD COMPUTING SYSTEM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Companies now have even another reason to think about shifting their data management systems to the cloud, owing to the modern age of "cloud computing." Based on previous successful cloud deployments, data management applications are a good match for the cloud. Cloud-based information management has a number of benefits, but it also has a number of disadvantages. This article provides an overview of cloud data management systems as well as a look at where researchers are currently focusing their efforts. Because cloud-based data management is always evolving, keeping an open attitude is essential. As the largest consumer of data management services, business is a prime candidate for further investigation. Research on cloud computing management information systems is a primary topic of this investigation. An extensive evaluation of management and business process journals is done in order to achieve the study's objectives. Because of this, it is necessary to get a deeper grasp of how information is sent. Systems function and how cloud-based information systems are evolving, results are examined. Based on the results of the evaluation, we've come to an agreement to use cloud-based MIS in our current investigation. Cloud-based management information systems (MIS) are becoming more popular with both small and large businesses (both public and private). That's why we're writing about cloud-based management information systems in this piece. Cloud-based MIS may be used in outsourcing and management because of its many benefits. When it comes to cloud computing, it's all about flexibility and scale not a new technology but one that is only now gaining traction, is being used by the majority of businesses as a means of storing and running their critical data. A focus on the most efficient method of data management is required in this case. When it comes to cloud data storage, Big Table and Data Store are two options that work in distinct ways. In order to achieve your goals, you must make use of the appropriate technologies